The Mediated Geography of Hegel (Revista Eletrônica Estudos Hegelianos, 2024)
It is still largely ignored that Hegelian dialect is of great assistance to comprehend the production and contestation of space. Hegelian philosophy can help to enrich geographical scholarship, although Hegel-the-geographer is yet to be discovered and properly recognised. Considering the metabolism of reason, the articulation between the particular and the universal, and the function of otherness in the production of space, among other socio-spatial processes, this article offers a brief comparative analysis between Hegel’s minor geography (the more explicit and immediate considerations of space, spatial dimensions and geometry) and the more substantial, major geography, that is immanent in the main body of his philosophical system. The great geographical accomplishment of Hegel – his major geographical contribution – is the detailed investigation into the pursuit of higher reason and on what constitutes the absolute.